OPTIMASI PERSEN BINDER, BEBAN KOMPAKSI, DAN SUHU SINTERING DALAM PEMBUATAN BATU BATA TINGGI ALUMINA MENGGUNAKAN APLIKASI RSM (RESPONSE SURFACE METHODOLOGY) - Dianawati, Erika Arum; Sirait, Phichiato; Wibawa, Aditya; Husaini; Aryanti, Putu Teta Prihartini (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2024)
PT Indonesia Chemical Alumina (ICA) is a company that produces 300,000 tons of chemical grade alumina (CGA) per year. Of this amount, there is an average of 15,000 tons that do not meet market specifications every year. Alumina that does not meet this specification is only piled up by PT. ICA and takes up space, so it is economically detrimental to the company because they have to provide space to accommodate it. In fact, this alumina has a very high Al2O3 content and is in the form of an alpha phase or α-Al2O3 which is the most stable phase at the highest temperatures, so it can be processed into useful materials and has high added value such as high alumina bricks through compaction and sintering. Process conditions such as percent binder, load during compaction and sintering temperature greatly affect the quality of the high alumina bricks produced. The purpose of this study is to optimize the process conditions for making high-alumina bricks by identifying the relationship between input variables and the measured responses and developing a prediction model for experimental variations that will be used in optimizing the process conditions for the manufacture of high alumina bricks. The Design Expert 7.0® program with Box-Behnken Design Response Surface Methodology (RSM) is used to research and select process conditions from a combination of factor levels that produce an optimal response. Based on RSM Box-Behnken Design it is known that the main effects of binder percentage, compaction load and sintering temperature are factors that greatly influence the response value of high alumina bricks. The optimal response value for high alumina bricks is a compressive strength of 8.2229 MPa, with a process condition of 3% binder percent, a compacting load of 10 tons and a sintering temperature of 1600ºC.